Silent peripheral neuropathy determined by high-resolution ultrasound among contacts of patients with Hansen's disease - Voltan, Glauber; Marques-Júnior, Wilson; Santana, Jaci Maria; Lincoln Silva, Claudia Maria; Leite, Marcel Nani; De Paula, Natália Aparecida; Bernardes Filho, Fred; Barreto, Josafá Gonçalves; Da Silva, Moises Batista; Conde, Guilherme; Salgado, Claudio Guedes; Frade, Marco Andrey Cipriani (Frontiers in Medicine, 2023)
Introduction Hansen's disease (HD) primarily infects peripheral nerves, with patients without HD being free of peripheral nerve damage. Household contacts (HHCs) of patients with HD are at a 5–10 times higher risk of HD than the general population. Neural thickening is one of the three cardinal signs that define a case of HD according to WHO guidelines, exclusively considering palpation examination that is subjective and may not detect the condition in the earliest cases even when performed by well-trained professionals. High-resolution ultrasound (HRUS) can evaluate most peripheral nerves, a validated technique with good reproducibility allowing detailed and accurate examination. Objective This study aimed to use the peripheral nerve HRUS test according to the HD protocol as a diagnostic method for neuropathy comparing HHCs with healthy volunteers (HVs) and patients with HD. Methods In municipalities from 14 different areas of Brazil we selected at random 83 HHC of MB-patients to be submitted to peripheral nerve ultrasound and compared to 49 HVs and 176 HD-patients. Results Household contacts assessed by HRUS showed higher median and mean absolute peripheral nerve cross-sectional area (CSA) values and greater asymmetries (ΔCSA) compared to HVs at the same points. Median and mean absolute peripheral nerve CSA values were higher in patients with HD compared to HCCs at almost all points, while ΔCSA values were equal at all points. Mean ± SD focality (ΔTpT) values for HHCs and patients with HD, respectively, were 2.7 ± 2.2/2.6 ± 2.2 for the median nerve, 2.9 ± 2.7/3.3 ± 2.9 for the common fibular nerve (p > 0.05), and 1.3 ± 1.3/2.2 ± 3.9 for the ulnar nerve (p < 0.0001). Discussion Considering HRUS findings for HHCs, asymmetric multiple mononeuropathy signs (thickening or asymmetry) in at least 20% of the nerves evaluated could already indicates evidence of HD neuropathy. Thus, if more nerve points are assessed in HHCs (14 instead of 10), the contacts become more like patients with HD according to nerve thickening determined by HRUS, which should be a cutting-edge tool for an early diagnosis of leprosy cases.